1998
DOI: 10.1046/j.1365-2648.1998.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' and nurses' perceptions of the quality of nursing care in Kuwait

Abstract: Using an exploratory research method and a purposive sample of 259 subjects (109 of whom were nurses and 148 patients), data were collected using an instrument consisting of the elements of the nursing process. Four hypotheses were tested, using the analysis of covariance and the t‐test The result of hypothesis I showed that there was no statistically significant difference in the perception of the quality of nursing care between the patients in the medical and surgical units of the five study hospitals. Hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…While there are studies reporting congruence in the way that staff and patients perceive quality (Redfern & Norman 1996, Al‐Kandari & Ogundeyin 1998), others have taken a contrary viewpoint (Ervin et al. 1992, Irurita 1999, Attree 2001, Bassett 2002).…”
Section: Resultsmentioning
confidence: 99%
“…While there are studies reporting congruence in the way that staff and patients perceive quality (Redfern & Norman 1996, Al‐Kandari & Ogundeyin 1998), others have taken a contrary viewpoint (Ervin et al. 1992, Irurita 1999, Attree 2001, Bassett 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In overall hospital care, nursing care is the most significant factor (Joiner, 1996; Williams, 1998; Al‐Kandari & Ogundeyin, 1998) and a high correlation has been found between satisfaction with nursing care and satisfaction with overall health care (Beck & Larrabee, 1996). Research has indicated that patient satisfaction is an important indicator of quality of care (Jacox et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to provide that kind of care, nurses must seek patients' perspectives on nursing care quality and incorporate them into routine quality evaluation as well as professional and organizational perspectives (Chang, 1997). Despite extensive research regarding quality in health care, relatively little attention has been given to the patients' perspectives (Joiner, 1996; Oermann, 1999; Radwin, 2000; Oermann & Templin, 2000) but such studies are emerging (Al‐Kandari & Ogundeyin, 1998; Redfern & Norman, 1999; Larsson, 1999; Koch et al. , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, because patients have no basis to compare with, they might have difficulty in evaluating what nurses provide to them 13 . Furthermore, the assessments of quality of health care represent a complex mixture of needs, expectations of care and the experience of care 9,14 …”
Section: Introductionmentioning
confidence: 99%